Admission NarxCare Narcotics Scores are not Associated With Adverse Surgical Outcomes or Self-reported Patient Satisfaction Following Elective Spine Surgery. Issue 21 (1st November 2019) - Galivanche, Anoop R.; Mercier, Michael R.; Adrados, Murillo; Pathak, Neil; McLynn, Ryan P.; Anandasivam, Nidharshan S.; Varthi, Arya G.; Rubin, Lee E.; Grauer, Jonathan N.
Abstract : Study Design: Retrospective cohort study Objective: The aim of this study was to investigate how elective spine surgery patient preoperative opioid use (as determined by admission NarxCare narcotics use scores) correlated with 30-day perioperative outcomes and postoperative patient satisfaction. Summary of Background Data: The effect of preoperative narcotics usage on postoperative outcomes and patient satisfaction following spine surgery has been of question. The NarxCare platform analyzes the patients' state Physician Drug Monitoring Program (PDMP) records to assign numerical scores that approximate a patient's overall opioid drug usage. Methods: Elective spine surgery cases performed at a single institution between October 2017 and March 2018 were evaluated. NarxCare narcotics use scores at the time of admission were assessed. Patient characteristics, as well as 30-day adverse events, readmissions, reoperations, and mortality, were abstracted from the medical record. Hospital Consumer Assessment of Healthcare Providers and Systems (HCAHPS) survey data were also abstracted when available. Cases were binned based on the following ranges of admission NarxCare scores: 0, 1 to 99, 100 to 299, 300 to 499, and 500+. Multivariate logistic regressions were performed to compare the odds of having an adverse events, readmission, reoperation, and mortality between the different narcotics groups. One-way analysis of variance analyses were performed to compare HCAHPS survey response rates and HCAHPS survey results between the different narcotics score groups. Results: In total, 346 patients met criteria for inclusion in the study (NarxScore 0: n = 74, 1–99: n = 58, 300–499: n = 117, and 500+: n = 21). Multivariate logistic regressions did not detect statistically significant differential odds of experiencing adverse events, readmission, reoperation, or mortality between the different groups of admissions narcotics scores. Analyses of variance did not detect statistically significant differences in HCAHPS survey response rates, total HCAHPS scores, or HCAHP subgroup scores between the different narcotics score groups. Conclusion: Although there are many reasons to address preoperative patient narcotic utilization, the present study did not detect perioperative outcome differences or patient satisfaction based on the narcotic use scores as stratified here. Level of Evidence: 3 Abstract : The effect of preoperative narcotics usage on postoperative outcomes and patient satisfaction has been of question. A retrospective cohort comparison study of patients with varying preoperative NarxCare narcotics scores undergoing elective spine surgery was performed (n = 346). Multivariate logistic regression failed to show correlation with perioperative adverse events. Analysis of variance failed to show association with patient satisfaction.